Systemic immune response and virus persistence after foot-and-mouth disease virus infection of naïve cattle and cattle vaccinated with a homologous adenovirus-vectored vaccine. Issue 1 (December 2016) - Eschbaumer, Michael; Stenfeldt, Carolina; Rekant, Steven; Pacheco, Juan; Hartwig, Ethan; Smoliga, George; Kenney, Mary; Golde, William; Rodriguez, Luis; Arzt, Jonathan
Abstract Background In order to investigate host factors associated with the establishment of persistent foot-and-mouth disease virus (FMDV) infection, the systemic response to vaccination and challenge was studied in 47 steers. Eighteen steers that had received a recombinant FMDV A vaccine 2 weeks earlier and 29 non-vaccinated steers were challenged by intra-nasopharyngeal deposition of FMDV A24. For up to 35 days after challenge, host factors including complete blood counts with T lymphocyte subsets, type I/III interferon (IFN) activity, neutralizing and total FMDV-specific antibody titers in serum, as well as antibody-secreting cells (in 6 non-vaccinated animals) were characterized in the context of viral infection dynamics. Results Vaccination generally induced a strong antibody response. There was a transient peak of FMDV-specific serum IgM in non-vaccinated animals after challenge, while IgM levels in vaccinated animals did not increase further. Both groups had a lasting increase of specific IgG and neutralizing antibody after challenge. Substantial systemic IFN activity in non-vaccinated animals coincided with viremia, and no IFN or viremia was detected in vaccinated animals. After challenge, circulating lymphocytes decreased in non-vaccinated animals, coincident with viremia, IFN activity, and clinical disease, whereas lymphocyte and monocyte counts in vaccinated animals were unaffected by vaccination but transiently increased after challenge. The CD4+ /CD8+ T cell ratio in non-vaccinated animals increased during acute infection, driven by an absolute decrease of CD8+ cells. Conclusions The incidence of FMDV persistence was 61.5 % in non-vaccinated and 54.5 % in vaccinated animals. Overall, the systemic factors examined were not associated with the FMDV carrier/non-carrier divergence; however, significant differences were identified between responses of non-vaccinated and vaccinated cattle.